THE RUSTY BUTLER ARCHIVE: REVELATIONS OF CULTURAL REPRESSION DURING THE BRAZILIAN MILITARY DICTATORSHIP - Calla J. C. Knapp; Rex P. Nielson (Revista Brasileira de Literatura Comparada, 2022)
The twenty-one years of military dictatorship in Brazil (1964–1985) were marked by severe repression as government censors sought to control media and artistic production. During these tense years, as has been well documented, journalists, academics, writers, and artists at times struggled to voice their opposition to oppressive military control. Many turned to protest theater as a way to speak out against the dictatorship’s abuses. Unsurprisingly, many plays produced at this time were either heavily censored or shut down entirely. In the late 1960s and early 1970s, a young Brazilianist scholar from the United States, Ross “Rusty” Butler, befriended, interviewed, and conducted field research on authors of protest theater and their works. When Butler was preparing to return to the United States after being threatened himself by government officials, a few of his new friends asked him to take their works—including some plays that were unpublished and in manuscript form—out of the country in order to avoid censorship. Now, fifty years later, those plays and manuscripts, along with Butler’s other research materials, are finally coming to light through the Rusty Butler Archive. The Rusty Butler Archive demonstrates the complex relationship between the military dictatorship, censorship, and cultural production during the 1960s and 70s.